The Seismic Resistance Analysis of Frame Structures and Wall Structures Using Ferrocement and Expanded Metal - Yossakorn Chonratana; Vuttichai Chatpattananan (My University, 2023)
This article presents a study of the use of ferrocement and expanded metal in the columns, beams, and walls of a reinforced concrete building structure to increase its seismic resistance. This study focused on a concrete building with three stories, located in Thailand. In the design of the reinforcement structure, a calculation and analysis of seismic resistance were conducted in a comparison of the original concrete building structure with the reinforced concrete building structure using the nonlinear static force method (pushover analysis method). The results showed that the seismic resistance of the reinforced concrete building structure was higher than the design value (DPT), with different seismic resistance values for the reinforced frames, columns, and walls of approximately 14%, 81%, and 19%. In particular, it had increased stiffness values for the frames, columns, and walls and increased ductility values for the walls. Moreover, the seismic resistance values originating from the reinforcement were significantly higher than those of the concrete building structure. Therefore, reinforcement should be applied to all concrete building structures with the implementation of the damage index, ensuring that it is reduced to the allowable level.
Keywords: Ferrocement; Seismic resistance; Ductility (Earth science); Structural Behavior of Reinforced Concrete